The competitive position of farms according to class of economic size - Nowak, Anna (Konkurencyjność wynikowa gospodarstw rolnych w zależności od ich wielkości ekonomicznej, 2020)
This paper aimed at evaluating the competitive position of farms in Poland according to class of economic size. The study was carried out based on data from the European system for collecting accounting data on farms, i.e. EU FADN, for 2015-2017. The analysis made use of work profitability ratios and partial productivity indicators referring to production factors. The studies revealed a relationship between the economic power of farms and the efficient utilisation of production factors. Economically stronger farms had a competitive advantage as regards the productivity of land, labour and capital, as well as work profitability. The conclusion is that continuing structural transformations in agriculture to optimise the structure of farms is justified. It was also demonstrated that Polish farms in respective classes of economic size were less competitive than their equivalents in the European Union
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 57-66
Keywords: farms; competitive position; economic size; productivity; gospodarstwa rolne; konkurencyjność wynikowa; wielkość ekonomiczna; produktywność